Application of accounting regulations and income tax evasion in México - Amezcua Luján, Martha Karina (Universidad de Sonora, 2020)
The objective is test whether of the application accounting regulations contribute the ISR income tax evasion in Mexico. A observational descriptive study cross cut was realize and the qualitative analysis of several  legal precepts contained in the Ley del Impuesto Sobre la Renta Renta (“Mexican Income Tax Law” or “LISR”), as well as regulatory criteria in the tax sphere, sampling and comparing companies or taxpaying legal entities or individuals subject to both the income tax and the fulfillment of their fiscal duties, such as bookkeeping and applying accounting rules, the quantitative analysis was performed on the data obtained from economic censuses by applying statistical methods. The results prove that tax evasion was lower in legal entities that are obliged to apply accounting regulations in accordance with the income tax, compared to individuals subject who are not obliged to apply such regulations. It is recommended the further study of the fiscal impact. It is concluded that the non-application of the accounting normative is a cause of increased fiscal evasion of ISR in Mexico.